Pacific Basin industries in distress : (Columbia University Press, 1991)
Presents case studies of how North American, Asian, and Oceanic governments have intervened to help ailing industries, and the impact their actions have had on the industry, the country's economy, and the growth of free trade. The primary goal is to find alternatives to knee-jerk import controls.